THE ONTOLOGICAL AND INTELLECTUAL DIMENSIONS OF LOVE IN IBN SINA'S THOUGHT - Muhammad Fadhail Itsar Muwasah Al-Haq; Mutiara MY (ISSUE: Journal of Islamic Studies for Universal Dialogue, 2025)
Love in general is a term often used to describe kindness and affection. Ibn Sina observed that love in human life except for spiritual love toward God is always connected to temporary and worldly objects. According to Ibn Sina, true love is intellectual love which is not bound to physical aspects but focused on seeking the Divine essence and the perfection of the rational soul. This idea aligns with earlier philosophers like Plato who believed that true love should be directed toward an eternal and limitless object. In his works Ibn Sina distinguishes between two main types of love: sensual love and intellectual love. Sensual love is driven by desires and physical attraction making it temporary and ever-changing. In contrast intellectual love arises from understanding the beloved object not based on outward appearance but on essence and reality. In this context love is seen as an emanative process that flows from the First Source God toward lower entities including the human soul. Intellectual love according to Ibn Sina is an everlasting form of love that brings the soul closer to perfection and a deeper understanding of God. Love for God as the manifestation of the Divine essence serves as the main driving force in the spiritual and intellectual journey of humans toward perfection.